FRAUD LAPORAN KEUANGAN: PREVENTIF TERHADAP FRAUD PADA PERUSAHAAN - Leni Laudeciska; Yanni Yanni; Yunita Yunita (Jurnal Bina Akuntansi, 2023)
Economic losses due to fraud financial statements have harmed the organization and the community. This is due to the limitations of risk management strategies available in efforts to prevent financial statements fraud by company managers and auditors, this strategy is able to prevent fraud proactively and help build future financial statements. This multi-case qualitative research aims to explore early detection and the authors use the conceptual framework of risk management in prevention of fraud over financial statements. Therefore, it can be concluded that there is a gap in the concept of risk management in current practice to detect and prevent fraud, as well as the auditor's perspective in creating proactive anti -fraud models. In addition, with this finding the auditor can also develop early detection guidelines, and practitioners can develop anti-fraud risk management procedures.